Yolk sac tumor in an antenatal patient: a challenging case - Namgyal, Anu; Soni, Anjali; Verma, Suresh; Chauhan, Indu; Sharma, Shikha; Purbia, Charu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Pregnancy complicated with adnexal masses is a very common occurrence. However, most of these adnexal masses encountered in pregnancy are benign in nature and are found incidentally during routine antenatal ultrasound. Malignant ovarian neoplasms account for 1%-8% of all persistent adnexal masses diagnosed during pregnancy. Yolk sac tumor (YST) complicating pregnancy is very rare and has no proper guidelines for its diagnosis and management hence causing a therapeutic dilemma for the clinicians. Therefore, an individualised approach is preferred in such cases. It is very important to report such cases for better understanding and management of these cases. Here we present a case report of a 23-year-old primigravida at 30 weeks gestation with yolk sac tumor of right ovary, surgical stage IIIc who responded well to fertility sparing surgery with cisplatin-based combination chemotherapy. She has no evidence of disease post treatment and has been put on regular follow up.